Philosophy of nature and spaces of hope in David Harvey - Barahona Riera, Dorelia (2023)
The city has always been a landscape that shapes us socially. Its spaces provide us with health, emotions, rights — or, alternatively, exclusion, isolation, illness, and economic, social, and even aesthetic poverty. The city produces both material and symbolic inequality. Spaces such as domestic gardens and public parks can serve as places of hope and restoration. We propose the idea of an 'emotional and restitutive city,' where territorial equality and epistemic justice are put into practice through social ecology and the thought of David Harvey